Decreased Thymic Output Contributes to Immune Defects in Septic Patients - Sommer, Natascha; Noack, Steffen; Hecker, Andreas; Hackstein, Holger; Bein, Gregor; Weissmann, Norbert; Seeger, Werner; Mayer, Konstantin; Hecker, Matthias (Journal of Clinical Medicine, 2020)
Background: Prolonged immunosuppression and hypoinflammation, termed compensatory anti-inflammatory response syndrome (CARS), contribute to high morbidity and mortality in the late phase of sepsis. Although apoptosis is a well-known cause of lymphopenia in sepsis, the contribution of thymic output to immune alterations in sepsis and potential compensatory mechanisms are largely unknown. Methods: We investigate the release of CD4+ T cells from the thymus and their peripheral proliferation by evaluating T-cell receptor excision circles (TREC) and the expression of CD31 as markers for recent thymic emigrants (RTE) and their proliferative offspring in septic patients with relevant lymphopenia in the CARS phase. Moreover, we determine the aging of T cells by measuring telomere characteristics. Results: In septic patients, we found decreased CD4+ T-helper cell numbers, while CD8+ T cell numbers were unchanged. As a possible cause, we detected increased apoptosis of CD4+ T-helper cells and decreased levels of IL-7, which promotes the maturation of T cells in the thymus. Accordingly, the relative number of mature CD4+ T cells, TREC-containing CD4+ T cells, and CD31+ RTEs (characteristic of thymic output) was decreased, while the relative number of CD31-T cells (peripherally expanded naive T cells) was increased. Furthermore, the telomere length decreased, although telomerase activity and markers for the shelterin complex were increased specifically in CD4+ but not in CD8+ T cells. Conclusion: We thus conclude that, in addition to T-cell apoptosis, decreased thymic output and increased aging of CD4+ T cells may contribute to lymphopenia and immunosuppression in sepsis. Increased proliferation of peripheral T cells cannot compensate for these effects.
CRIS-Team WoS Importer:2020-11-06